Preparation of Financial Reports by Following SAK EMKM in the Era of Society 5.0 at UD. Modern Truss - Jasmaulani, Galuh Ayu; Rahayu , Duwi (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Financial reporting is critical for the success of Micro, Small, and Medium Enterprises (MSMEs), particularly in the Society 5.0 era, where digital literacy and technological adoption are essential for competitiveness. Specific Background: MSMEs must align their financial practices with reliable standards like the Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) to enhance transparency and efficiency in financial information management. Knowledge Gap: Despite the significance of financial reporting, many MSMEs, including UD. Modern Truss, a construction services and building materials business, have not yet adopted SAK EMKM in their financial practices, leading to simplistic and incomplete reporting. Aims: This research aims to provide MSME owners with information on how to prepare financial reports according to SAK EMKM, in line with the evolving Society 5.0 era's emphasis on technology and transparency. Results: The findings reveal that UD. Modern Truss has not yet implemented financial reporting in accordance with SAK EMKM, relying only on basic records of sales and purchases. The study also presents financial reports for the company, including a financial position report, profit and loss statement, and statement of changes in capital for the period January to December 2022. Novelty: This research offers practical insights into the challenges faced by MSMEs in adopting SAK EMKM standards, providing a framework for improved financial reporting. Implications: The results underscore the need for MSMEs to adopt proper financial reporting standards, enhancing financial transparency and supporting future research on the digital transformation of MSME financial practices. Highlights: UD. Modern Truss has not yet implemented SAK EMKM standards in its financial reporting. The study provides financial reports for January to December 2022, including profit and loss and capital changes. Adopting SAK EMKM is crucial for MSMEs to achieve transparency and improve financial management. Keywords - Financial Reporting, MSMEs, SAK EMKM, Society 5.0, Transparency